TAWARAN LANGSUNG YANG DILAKUKAN BIDAN BERPENGARUH TERHADAP PEMBERIAN SUSU FORMULA KEPADA BAYI BARU LAHIR - ., Sukamto; Bruh, Rasidah Huraini; Adi, M. Sakundarno (Universitas Pekalongan, 2015)
In 2010, the supply of exclusive breast milk in Medan is very low. It is only 3,04% of infants who get exclusive breast milk. Low supply of this exclusive breast milk is caused by the private practice midwives’ behavior in giving formula milk for newborns. This study is aimed to analyze the influence of personal selling performed by private practice midwives who give formula milk feeding for newborns. Methods : This type of research is explanatory research which is aimed to analyze the effect of the personal selling performed by private practice midwives who give formula milk feeding for newborns. The writer used survey method with cross sectional approach. Results : Three variables that were significantly associated to formula breastfeeding to neonatal infants are personal selling (p<0,05), knowledge and attitude. Conclusion : The results show that the personal selling has dominant influence toward formula milk feeding for newborns. The writer suggests the private practice midwives to provide correct and clear information about exclusive breast milk. Keywords : Formula Milk , Personal Selling , Private Practice Midwife